Analisis Kualitas Pelayanan Jasa Rumah Makan Tahu Pong Dan Mie Keriting Brumbungan Dengan Metode Servqual - Devina Nathania Hamdoko; Veronica Kusdiartini (JEMAP, 2022)
Service quality was a problem faced by Tahu Pong and Mie Keriting Brumbungan Restaurant because there were consumer complaints about it. This study aimed to determine the gap between expected service and perceived service by consumer, the gap between expected service and management's perception of expected service, and determine the level of importance and performance of restaurant’s service. Method used was servqual through gap analysis number one and five. It was analyzed by Independent Sample t-test to know whether the gaps have significant differences or not. It was used Importance Performance Analysis (IPA) in order to know the level of importance and performance, which was depicted in the Cartesian diagram. The data was primary data obtained by questionnaires. The results found that there was a gap five, meaning the quality of service at the restaurant was not in accordance with consumer expectations. The biggest difference was significant in the tangibles dimension. While the smallest gap lies in the empathy dimension and there was no significant difference. There was no difference between consumer expectations and management's perception of consumer expectations (gap one). In the Importance Performance Analysis, the main priority was to improve on some service quality attributes X1.3, X1.5, X3.1, X3.5, dan X4.5. As for the suggestions for the restaurant in improving the quality of service, namely the leadership to carry out preventive maintenance and breakdown maintenance, provide directions to parking attendants to improve the efficiency of parking space, provide health protocol equipment and provide directions on how to use it properly, recruit new employees as servants. Further research analysis of service quality needed using the entire gap.